(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Strengtheningfinancial systems has been one of the central issues facing emerging marketsand developing economies. This is because sound financial systems serve as animportant channel for achieving economic growth through the mobilization offinancial savings, putting them toproductive use and transforming various risks (Beck, Levin and Loayza 1999; King andLevin 1993; Rajan and Zingales1998; Demirgüç-Kunt, Asli and Maksimovic 1998; Jayaratne and Strahan 1996). Many countries adopted a series of financial sector liberalizationmeasures in the late 1980s and early 1990s that included interest rate liberalization, entry deregulations, reduction of reserve requirements and removal of credit allocation. In manycases, the timing of financial sector liberalization coincided with that ofcapital account liberalization. Domestic banks were given access to cheap loansfrom abroad and allocated those resources to domestic production sectors.